Political parties and congressional processes in Spain. An approach from participant observation and political communication to the Congresses of PSOE and Podemos. - Sánchez Duarte, José Manuel; Calvo, Dafne (Cuadernos de Gobierno y Administración Pública, 2018)
Inner workings of political parties, assemblies and internal elections have been adapted to new forms of political communication and the establishment of the permanent campaign. Despite of being conceived as a formula to reflect on the internal operations of organizations, congressional processes are also designed as events where the electorate meets and loyalizes with the party and its leader. Thus, affiliate mobilization and internal communication bear similarities with the electoral periods in terms of media visibility and organizational importance. In terms of strategy, this is due to their ability to condition the functioning of organizations in periods between elections. The following article presents the results of participant observation in national congresses for the election of leaders and programs in PSOE and Podemos. The main objective is to identify the motivations of the participants by sharing their natural environment. Another purpose is to understand the development of these events from the perspective of political communication. This investigation exposes the difficulties encountered for the application of this type of methodology as well as the identification of these congresses as cultural exhibitions, “political leisure” activities and media events.
Keywords: Congresses; Political Parties; Political Communication; Participant observation.